Rice Straw Vermicompost Enriched With Cellulolytic Microbes Ameliorate the Negative Effect of Drought in Wheat Through Modulating the Morpho-Physiological Attributes - Ahmad, Ali; Aslam, Zubair; Hussain, Saddam; Bibi, Amir; Khaliq, Abdul; Javed, Talha; Hussain, Sadam; Alotaibi, Saqer S.; Kalaji, Hazem M.; Telesiński, Arkadiusz; Iwai, Chuleemas Boonthai; Kumar, Uttam (Frontiers in Environmental Science, 2022)
Wheat growth and productivity are unfavorably pretentious by lack of sufficient water (drought or water deficit) worldwide. Hydrological drought significantly affects all the morpho-physiological and biochemical characteristics and agronomical yield of wheat. Different management approaches have been adopted to cope with the negative effects of water deficit. Soil applied vermicompost is helpful in improving the growth and developmental processes of wheat under water deficit conditions. Therefore, a trial was carried out to optimize the best amount of vermicompost and to assess its role in ameliorating the negative effects of drought for sustainable crop production. The treatments consisted of (a) two contrasting wheat cultivars Faisalabad-08 (drought-tolerant) and Galaxy-13 (drought-sensitive), (b) drought with three levels [D0= 70% of field capacity (no drought), D1= 45% of field capacity (mild drought), D2= 30% of field capacity (severe drought)] and (c) cellulolytic microbes enriched vermicompost prepared from rice straw with four levels (VT0= Control, VT1= 4 t ha-1, VT2= 6 t ha-1 VT3= 8 t ha-1). Data on various morphological, physiological, and biochemical parameters were recorded from sowing to crop harvesting. In this study, it was demonstrated that all these parameters are negatively affected by moisture deficit conditions. The application of vermi-fertilizer significantly increased (p < 0.05) the above-mentioned parameters of wheat in both the absence and presence of drought. We concluded that the application of vermicompost is a valuable approach to alleviate the adverse impacts of water stress on wheat.